Comparison of gingival biotype in smokeless tobacco users (Gutka and Paan) and non-tobacco users - Prena Moorpani; Fazal Ur Rehman Qazi; Shahbaz Ahmed Jat; Hira Akhtar; Munazza Aziz; Marina Shah (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the gingival biotypes in smokeless tobacco (Gutka and Paan) users and compare it with non-tobacco users in Karachi sub-population using trans-gingival probing method (TRAN). Methods: This in-vivo, cross sectional study was conducted in the department of Operative Dentistry from 20th February 2019 to 25th June 2019 Dow University of Health Sciences, Karachi after obtaining ethical approval from the Institutional review board of DUHS (Ref: IRB-1207/DUHS/Approval/2019/21). A total of 70 participants, 35 subjects currently using smokeless tobacco (Gutka and Paan) and 35 non-tobacco users from both genders were included in the study after taking informed consent. Gingival biotype was recorded using probe transparency method. Probing of the gingival sulcus was performed at the mid-buccal aspect of both maxillary incisors. Depending on the visibility of the underlying probe gingiva was categorized as thin or thick. Results: Statistically significant differences in gingival biotype was observed of both groups (p=0.005). Males were recorded with a higher percentage of thick gingiva in both groups (81% in smokeless tobacco and 65% in non-tobacco) while in females thick gingiva was more prevalent in smokeless tobacco group (85.7%) whereas thin gingiva was noted in non-tobacco group (66.7%); although the results between genders was statistically insignificant. The comparison between different age groups, genders and both groups was statistically insignificant. Conclusion: Significant difference was observed between gingival biotype of smokeless tobacco and non-tobacco user groups. No statistically significant results were observed between genders and age groups. Keywords: Gingival biotype, smokeless tobacco, Continuous...